2020
DOI: 10.1084/jem.20200298
|View full text |Cite
|
Sign up to set email alerts
|

Serum HBsAg clearance has minimal impact on CD8+ T cell responses in mouse models of HBV infection

Abstract: Antibody-mediated clearance of hepatitis B surface antigen (HBsAg) from the circulation of chronically infected patients (i.e., seroconversion) is usually associated with increased HBV-specific T cell responsiveness. However, a causative link between serum HBsAg levels and impairment of intrahepatic CD8+ T cells has not been established. Here we addressed this issue by using HBV replication-competent transgenic mice that are depleted of circulating HBsAg, via either spontaneous seroconversion or therapeutic mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…The results reported here are noteworthy considering that steady-state KC cross-presentation of HBV Ags is an inefficient process that cannot be increased by liver inflammation, hepatocellular death, or the administration of therapeutic monoclonal antibodies directed against HBsAg leading to the generation of circulating immune complexes ( Fumagalli et al., 2020 ). Our data do not rule out a direct effect of IL-2 on T cells; however, they indicate that optimal in vivo reinvigoration of intrahepatically primed T cells by IL-2 depends on the presence of KC2.…”
Section: Discussionmentioning
confidence: 88%
“…The results reported here are noteworthy considering that steady-state KC cross-presentation of HBV Ags is an inefficient process that cannot be increased by liver inflammation, hepatocellular death, or the administration of therapeutic monoclonal antibodies directed against HBsAg leading to the generation of circulating immune complexes ( Fumagalli et al., 2020 ). Our data do not rule out a direct effect of IL-2 on T cells; however, they indicate that optimal in vivo reinvigoration of intrahepatically primed T cells by IL-2 depends on the presence of KC2.…”
Section: Discussionmentioning
confidence: 88%
“…5 In contrast, another study showed that HBsAg clearance was not associated with increased antiviral T cell responses after interleukin-2-based immunotherapeutic intervention. 14 Understanding which viral and host factors are associated with the HBV-specific immune response, it is very important to identify biomarkers that can be used to select and stratify patients for clinical trials investigating novel therapeutic strategies aimed at functional cure. In addition to HBsAg, other viral proteins could potentially have an impact on the immune response.…”
Section: Hepatologymentioning
confidence: 99%
“…In order to determine the role of circulating and intrahepatic HBsAg in the induction of CD8+ T cell exhaustion, Fumagalli and colleagues reported recently that serum HBsAg clearance induced by either spontaneous seroconversion or therapeutic monoclonal antibodies has only a minimal effect on the expansion of HBV-specific naive CD8+ T cells undergoing intrahepatic priming (54). Interestingly, another study by this research group with transgenic mice expressing high level of HBcAg in almost all the hepatocytes and mice expressing lower level of HBcAg in approximately 10% of hepatocytes by adenoviral transduction showed that adoptively transferred HBcAg-specific naïve CD8+ T cells failed to differentiate into effector CTLs in mice expressing either high or low levels of HBcAg in hepatocytes (50).…”
Section: Effects Of Reducing Intrahepatic Viral Protein Expression And/or Circulating Hbsag On Antiviral Immune Responses In Mouse Modelsmentioning
confidence: 99%